The Development of Canva-Based Gamified Interactive Learning Media to Support Early Arabic Reading Literacy for Children Aged 4-5 Years - Munawaroh, Iin Rosdiana; Astuti, Wili (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Objective: This study aims to develop and evaluate the feasibility of a gamification-based interactive learning media created with Canva to support early Arabic reading instruction for children aged 4-5 years. The media is designed to enhance learning engagement, strengthen recognition of Hijaiyah letters, and support children’s ability to identify letter shapes and sounds through visually appealing and interactive digital learning experiences suited to early childhood developmental characteristics. Method: This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. During the development stage, the learning media was created using Canva and integrated with gamification elements such as step-by-step learning progression, visual rewards, simple navigation, and child-friendly visual design. The product was validated by experts in three aspects: content feasibility, instructional and media design, and language appropriateness. Data were collected using Likert-scale questionnaires and analyzed descriptively to determine the validity level of the developed media. Results: The validation results showed that all assessed aspects content feasibility, instructional and media design, and language appropriateness obtained an average score of 4.00, categorized as very valid. The Aiken’s V coefficient for all aspects was 0.75, indicating a high level of content validity and strong agreement between experts. Minor revisions were suggested, particularly in simplifying game instructions and enhancing visual variation to better suit young learners. These findings suggest that the Canva-based gamified interactive media is suitable for use in early Arabic reading instruction for children aged 4-5 years and has the potential to create a more engaging, enjoyable, and participatory early learning experience. Conclusion: The developed gamification-based interactive learning media is considered valid and feasible as a digital learning resource for introducing early Arabic reading skills to children aged 4-5 years. Its visual and interactive features make it a promising tool for increasing learning motivation and supporting early literacy development. Further research is recommended to examine the effectiveness of this media in improving children’s reading outcomes in direct classroom learning contexts.